Pengembangan Media Pembelajaran Virtual Reality (VR) Berbantuan Millealab Terhadap Pemahaman Konsep Matematis Siswa - Darwanto; Dwi Paramita (Universitas Muhammadiyah Kotabumi, 2025)
The problem in this study is the low conceptual understanding of class VII A students of MTs Negeri 1 Lampung Utara. The purpose of this study was to obtain virtual reality learning media assisted by MilleaLab for understanding mathematical concepts of line and angle material, to determine the feasibility of virtual reality learning media assisted by MilleaLab for understanding mathematical concepts of line and angle material, and to determine the effectiveness of virtual reality learning media assisted by MilleaLab for understanding mathematical concepts of line and angle material. The method used in this study is Research and Development (R&D) with the ADDIE model. The research procedure begins with interviews with students to identify student needs, continues with the development of appropriate VR media, and ends with field trials using measuring instruments to measure the effectiveness of the media. The results showed that the use of VR learning media effectively helped MilleaLab in improving students' understanding of mathematical concepts, with an N-Gain score of 0.79 which is included in the